Structure and specificity of T cell receptor gamma/delta on major histocompatibility complex antigen-specific CD3+, CD4-, CD8- T lymphocytes (The Rockefeller University Press, 1988)
Analyses of TCR-bearing murine and human T cells have defined a unique subpopulation of T cells that express the TCR-gamma/delta proteins. The specificity of TCR-gamma/delta T cells and their role in the immune response have not yet been elucidated. Here we examine alloreactive TCR- gamma/delta T cell lines and clones that recognize MHC-encoded antigens. A BALB/c nu/nu (H-2d)-derived H-2k specific T cell line and derived clones were both cytolytic and released lymphokines after recognition of a non-classical H-2 antigen encoded in the TL region of the MHC. These cells expressed the V gamma 2/C gamma 1 protein in association with a TCR-delta gene product encoded by a Va gene segment rearranged to two D delta and one J delta variable elements. A second MHC-specific B10 nu/nu (H-2b) TCR-gamma/delta T cell line appeared to recognize a classical H-2D-encoded MHC molecule and expressed a distinct V gamma/C gamma 4-encoded protein. These data suggest that many TCR-gamma/delta-expressing T cells may recognize MHC-linked antigens encoded within distinct subregions of the MHC. The role of MHC- specific TCR-gamma/delta cells in immune responses and their immunological significance are discussed.